Psychometric Properties of Turkish versions of the Leyton Obsessional Inventory-Child Version (LOI-CV) and Obsessive Beliefs Questionnaire-Child Version (OBQ-CV). Issue 4 (1st December 2016) - Boysan, Murat; Kadak, Muhammed Tayyib; Tarakcioglu, Mahmut Cem; Sertdurak, Zeynep Seda; Demirel, Omer Faruk
ABSTRACT: Objective: Juvenile obsessive-compulsive disorder has been increasingly recognized in the literature. However, the developmentally sensitive screening tools for obsessive-compulsive disorder (OCD) in children and adolescents still lag behind psychometric tools developed for adult OCD. The Leyton Obsessional Inventory-Child Version is the most widely utilized screening tool for juvenile OCD assessment. Our aim was to assess psychometric properties of the Leyton Obsessional Inventory-Child Version (LOI-CV) and Obsessive Beliefs Questionnaire-Child Version (OBQ-CV). Method: The sample consisted of 805 children and adolescents, aged from 11 to 17 years. Mean age of the sample was 13.85 (SD±1.40) years. The LOI-CV, OBQ-CV, Obsessive Compulsive Inventory-Revised (OCI-R), State Trait Anxiety Inventory for Children (STAI-C) and Meta-Cognitions Questionnaire for Children (MCQ-C) were completed by respondents. The data were subjected to explanatory and confirmatory factor analyses. Internal consistency and two-week temporal stability of scale scores were computed. Results: Explanatory and confirmatory factor analyses yielded a three-factor solution for the LOI-CV: Compulsions, Obsessions and Mental Neutralizing. Internal reliability was high for the overall scale (a=0.86) and sub-scales (Cronbach alphas= 0.76, 0.75, and 0.70, respectively). Factor analyses suggested a new three factor solution for the OBQ-CV: Responsibility/ Threat Estimation, Certainty/Control of Thoughts and Perfectionism. Internal consistency was excellent for the total measure (a=0.90) and the subscales (a=0.84, 0.82 ve 0.71, respectively). Retest reliability was high for the both LOI-CV (r=0.83) and OBQ-CV (r=0.78). Both of the measures revealed good convergent validity with the OCI-R, STAI-C, and MCQ-C. Conclusion: The LOI-CV and OBQ-CV had promising psychometric properties in a community sample of Turkish children and adolescents.